1995
DOI: 10.1074/jbc.270.43.25928
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for the Immunoglobulin-like Domain of Granulocyte Colony-stimulating Factor Receptor in Formation of a 2:1 Receptor-Ligand Complex

Abstract: The extracellular portion of the granulocyte colonystimulating factor (G-CSF) receptor has a mosaic structure of six domains (each approximately 100 amino acid residues) consisting of an immunoglobulin-like (Ig) domain, a cytokine receptor homologous region subdivided into amino-terminal (BN) and carboxyl-terminal (BC) domains, and three fibronectin type III repeats. In the present study, we expressed the Ig-BN and the BN-BC regions and purified them to homogeneity as monomers using G-CSF affinity column chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
28
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 28 publications
5
28
0
Order By: Relevance
“…However, it is not yet clear whether there are one or two ligand-binding sites on the G-CSF-R. Horan et al (14,15) concluded that there is probably one ligand-binding site with dimerization caused by receptor-receptor interaction. On the other hand, studies on the complexes formed with G-CSF and two soluble receptor fragments (Ig-BN and the CRHM) indicated that each G-CSF-R in the complex has two binding sites for G-CSF, one in the CRHM and one requiring the Ig domain (19). In addition, this study established that the Ig domain of the G-CSF-R is required for receptor dimerization (19).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…However, it is not yet clear whether there are one or two ligand-binding sites on the G-CSF-R. Horan et al (14,15) concluded that there is probably one ligand-binding site with dimerization caused by receptor-receptor interaction. On the other hand, studies on the complexes formed with G-CSF and two soluble receptor fragments (Ig-BN and the CRHM) indicated that each G-CSF-R in the complex has two binding sites for G-CSF, one in the CRHM and one requiring the Ig domain (19). In addition, this study established that the Ig domain of the G-CSF-R is required for receptor dimerization (19).…”
mentioning
confidence: 86%
“…In both these studies, Glu 19 in the A helix of G-CSF was identified as particularly important and appeared to be a possible candidate for interaction with Arg 288 . In the present study, to identify which G-CSF residues interact with Arg 288 in the receptor, we have mutated Glu 19 , Lys 23 , Glu 46 , and Asp 112 and compared the activity of these G-CSF mutants on cells expressing wildtype (WT) and mutant (R288A) receptors. In addition, to clarify further whether there are one or two binding sites on G-CSF, a chimeric receptor was constructed in which the Ig domain of gp130 replaced the G-CSF-R Ig domain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have taken into account that the extracellular region of gp130 has the same modular structure as the G-CSFR , Hibi et al, 1990Larsen et al, 1990), including an Ig-like domain that is lacking in the GHR (Leung et al, 1987). Both the Ig-like domain and the CBD of the G-CSFR are required for ternary complex formation with G-CSF (Hiraoka et al, 1995). In agreement with our model, we have recently identified neutralizing mAbs that recognize the Ig-like domain of gp130 (A. Hammacher & R.J. Simpson, in preparation) and interfere with the biological activity of IL-6 Wijdenes et al, 1995;Chevalier et al, 1996).…”
Section: The High Affinity Ternary Il-6 Receptor-complex Is a Hexamermentioning
confidence: 99%
“…The Ig-like module of gp130 (domain 1) has been shown to be involved in the interaction of gp130 with ligands that induce homodimerization of gp130 (IL-6 (35,36) and IL-11 (37)) and essential for the formation of high affinity hexameric complexes (15,35). This domain is thought to bind site III in IL-6 and IL-11 (35), and Ig-like modules in the GCSFR and LIF receptor are also thought to make contact with their cognate ligands (38,39). The three membrane-proximal FN III modules of gp130, although not directly involved in ligand binding, may be required for gp130 dimerization by ligands such as IL-6 (40) and IL-11 (41) or transmembrane signaling events such as stabilization and/or orientation of transmembrane receptor dimers (5).…”
mentioning
confidence: 99%